Molecular targets for altering radiosensitivity: lessons from Ras as a pre-clinical and clinical model. - Cengel, K; Mckenna, W (2005)
Ras activation has been correlated with malignant and metastatic cancer phenotypes and poor prognosis for cancer patients. In the preclinical setting, Ras activation by mutation or EGFR amplification results in increased clonogenic cell survival and decreased tumor growth delay following irradiation. Activation of the Ras pathway has also been associated with increased risk of local failure and decreased overall survival in patients receiving radiotherapy. Prenyltransferase inhibitors target the post-translational processing of Ras and have been shown to increase the radiosensitivity of human cancer cell lines. In the clinical setting, these inhibitors have been used with concurrent radiotherapy in a small number of phase I clinical trials with acceptable toxicity. Therefore, inhibiting Ras activation represents a promising molecular approach for radiosensitization in cancer therapy.